Prevalence and impact of falls as domestic injury among rural housewives of Raipur District, Chhattisgarh, India - Jaita Mondal; Maharaj Singh (Occupational Health and Safety Society of Nepal, 2023)
Introduction: The most common domestic injury among housewives is falling from stairs and ramps or on the floor. The present study aimed to find and associate the prevalence of falls with various agents, risk factors causing falls and the impact of falls among rural housewives. Methods: A cross-sectional survey was carried out among 500 randomly selected housewives from rural areas of Raipur district, Chhattisgarh in the month of March to June 2019. Demographic data and information regarding the occurrence of falls, various agents & factors associated with falls were collected by questionnaires, lux meter, anemometer and sound level meter through interviews, and observation techniques. The Nordic questionnaire was used to assess the impact of falls. Collected data were analyzed by using SPSS 20 statistical package. Results: 295 out of 500 housewives had domestic injuries which included 12.8 % of fall injuries. Fall had a significant association with various physical agents like illumination in the living room (χ2=11.004, df=1), relative humidity of the kitchen (χ2=18.03, df=2) and presence of adequate natural light (χ2=11.232, df=1). Even various personal risk factors were significant causes of falls like wearing slippers on a wet floor (χ2=11.845, df=1), presence of open electric wires (χ2=4.84, df=1), self-cleaning of toilet & floor (χ2=11.371, df=1) and self-cooking (χ2=10.959, df=1). Heavy works like carrying water in a big container (χ2=6.025, df=1), working under direct sunlight (χ2=4.195, df=1), prolonged standing while cooking or on an agricultural field (χ2=32.073, df=1) and using of hand pump per day to draw water (χ2=42.329, df=1) were highly significant causes of domestic fall. Conclusion: Findings of the study concluded that fall was very much prevalent among housewives, and being at home still housewives are exposed to various agents and personal risk factors causing fall.